Changes in Physicochemical Properties and Enzyme Activities of Four Soils Following the Application of Alkaline Winery Wastewater over Three Simulated Irrigation Seasons - Mabongo, L.; Gestring, W.; Howell, C.L.; Elephant, D.E. (South African Journal of Enology and Viticulture, 2025)
The in-field fractional use (augmentation) of undiluted alkaline winery wastewater (WW) with raw water for the irrigation of grapevines can reduce the abstraction of water from natural resources and mitigate global water shortages. However, undiluted WW could pose a threat to soil function and enzyme activities, which are early soil quality indicators. Hence, this study used a pot experiment to compare changes in physicochemical properties and enzyme activities of four different soils irrigated with undiluted WW and municipal water (MW) over three simulated irrigation seasons. The soils were collected from the top 0 cm to 30 cm soil layer to which no WW had previously been applied – in the Stellenbosch (sandy loam and sand), Robertson (clay loam) and Lutzville (sand) regions. The water sources were MW, which served as the control, and undiluted WW, and they were both analysed before each irrigation event. Irrigation with undiluted WW resulted in larger increases in soil pH, electrical conductivity (EC) and exchangeable K and Na for all soils and simulated irrigation seasons. The activities of acid phosphatase, β-glucosidase and urease were negatively affected by the addition of undiluted WW. Changes in acid phosphatase activity were negatively correlated with changes in soil pH and EC, while changes in β-glucosidase activity were negatively correlated with changes in soil pH, EC and exchangeable K, Na and Mg. The pH had a dominant effect because of its influence on enzyme activities, precipitation reactions and the development of salinesodic soils. Root exudates, acidification from nitrogen fertiliser and the uptake of K by crops can mitigate the potential risk of using undiluted alkaline wastewater.